Os anjos podem ferir: um estudo sobre a violência intrafamiliar - Souza, Adriana Aparecida de (2009)
This work considers the comprehension of the intrafamiliar violence emphasizing violent mothers relationships with their children. The purpose is to understand the development of these relationships which turn into aggressive behavior of the mothers regarding family education. The research was carried out focusing on two aspects: analysis of the theoretical references and empirical research. The theoretical research was done through a bibliographic survey of subjects related to this study such as: the history of the family, motherhood and children, the intrafamiliar violence practiced by mothers against their children; as well as how those violent relationships emerge from family environment. We point out the Foucault s concept of discipline (FOUCAULT, 1975) and Caldeira s concept of circumscribed body (CALDEIRA, 2000). It was selected a sample of ten women to investigate the relationship between mother and son through a detailed interviews. Five mothers from this sample were denounced to the Tutelary Council and they were set in a so called Denounced Group. Similarly, the other five mothers, who live in the same social and cultural context of the selected families assisted by the Tutelary Council, were set in the Non-Denounced Group. Therefore, we work with representations of the own interviewers about the meaning of the pedagogic socializing discipline in their lives. Our priority was the study of case carried out with the denounced families for physical violence and with the other group in order to develop a comparative analysis of both groups. Such methodological choice is explained by the interest for understanding the violence between mothers and children. It is common to all mothers not to consider aggressive their behavior against their children. We observe that physical punishment is considered a way to discipline children and teenagers, hence that is perceived as necessary to repress, to control, and to adapt them. Thus, it is considered a necessary practice for education. However, the reason that made the community denounced against the mothers of the Denounced Group was due to those did not correspond to an ideal example of what was expected to be a mother (they took drugs, alcohol, and had several sexual partners), that is denounces were not for the physical violence itself. Therefore, those mothers were not denounced because they were not morally able to manage their children s education. The community tolerates the punishment against children, but not the amorality of the women, and they were denounced for disregarding their role as mothers